2022
DOI: 10.3390/foods11030253
|View full text |Cite
|
Sign up to set email alerts
|

Byproducts (Flour, Meals, and Groats) from the Vegetable Oil Industry as a Potential Source of Antioxidants

Abstract: The present study presents the use of photochemiluminescence assay (PCL) and 2,2 diphenyl-1-picryl-hydrazyl (DPPH), 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), the ferric reducing antioxidant power (FRAP), and cupric ion reducing antioxidant capacity (CUPRAC) methods for the measurement of lipid-soluble antioxidant capacity (ACL) of 14 different byproducts obtained from the vegetable oil industry (flour, meals, and groats). The research showed that the analyzed samples contain significant amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 87 publications
3
11
0
Order By: Relevance
“…The highest concentration of TPC was observed in the RF2 eggs (46.79 μg GAE/g) compared to RF0 (40.93 μg GAE/g). Although to our knowledge there are no studies in which rosehip meal was used as a natural antioxidant for PUFA-enriched eggs, our results are comparable with studies that used different natural sources like rosemary [ 48 , 49 ], seabuckthorn, and grapeseed meal [ 6 , 50 ]. Studies in which flaxseed meals combined with synthetic antioxidants like vitamin E, butylated hydroxyanisole (BHA), and butylated hydroxytoluene (BHT) ([ 51 , 52 ] are available, however, the consumers’ concern regarding their safety has motivated the food industry to seek natural alternatives [ 53 , 54 , 55 ].…”
Section: Discussionsupporting
confidence: 80%
“…The highest concentration of TPC was observed in the RF2 eggs (46.79 μg GAE/g) compared to RF0 (40.93 μg GAE/g). Although to our knowledge there are no studies in which rosehip meal was used as a natural antioxidant for PUFA-enriched eggs, our results are comparable with studies that used different natural sources like rosemary [ 48 , 49 ], seabuckthorn, and grapeseed meal [ 6 , 50 ]. Studies in which flaxseed meals combined with synthetic antioxidants like vitamin E, butylated hydroxyanisole (BHA), and butylated hydroxytoluene (BHT) ([ 51 , 52 ] are available, however, the consumers’ concern regarding their safety has motivated the food industry to seek natural alternatives [ 53 , 54 , 55 ].…”
Section: Discussionsupporting
confidence: 80%
“…e DPPH activity of the tested samples was 17.29 ± 1.23 mg AAE/g DM (rapeseed) and 4.61 ± 0.76 mg AAE/g DM (sunflower) (Table 2). Numerous studies have demonstrated that the antioxidant activity of seeds is strongly affected by the content of phenolic compounds, including TPC and TFC, and this relationship has been reported by other authors [58].…”
Section: Dpph Free Radical Scavenging Activitysupporting
confidence: 67%
“…Multescu et al [ 41 ] studied the phenolic content, the flavonoid content, and the lipid-soluble antioxidant capacity of 14 by-products (rapeseed meals, grape seed flour, sunflower meals, seabuckthorn flour, etc.) obtained in the vegetable oil industry.…”
Section: Introductionmentioning
confidence: 99%